Research as Organizing: On the Challenges, Precarity and Commitment of Movement Scholarship - Baker, Rae; Aiello, Daniela; Noterman, Elsa; Hernandez, Ashley; Johnson, Sterling; Chavez, Marina; Masuda, Jeff (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2025)
Community organizing as a mode of scholarly praxis remains marginal and undermined within academic institutions by approaches to scholarship that have been determined objective and professional (Raphael and Matsuoka 2023). Reflecting on this challenge is a crucial priority among new generations of movement-scholars who encounter institutions that are content with reproducing the neoliberal academic status quo, signaled by growing labour precarity, extractive knowledge practices, and the metastasizing bureaucratization of higher education (Brackmann 2015). To integrate the praxis of community organizing or ‘movement work’ into one’s scholarly practice is often viewed as an affront to the objective distance and command for unbiased approaches to research demanded by institutional research ethics boards and even peer review processes. Movement scholarship is an approach to research that reinforces the material and political goals of social movements and spaces above knowledge production, and a stark contrast to traditional paradigms of research. Inspired by a roundtable held during the 2023 AAG, here we take up the challenges of movement scholarship as a paradigm of research that enables a scholarly praxis we conceptualize as ‘Research as Organizing’. We focus on: (1) the practice of research as organizing through movement scholarship, (2) the barriers faced to achieving traditional definitions of scholarly success through a movement-orientation, and (3) how movement scholarship can be supported through relational and institutional shifts within academia. We understand this shift as being central to recapturing the “radical geography spirit” (Castree 2000) and commanding space within the discipline and academic institutions at large.